2014
DOI: 10.1111/vop.12186
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment morphology and morphometry in selected reptile species using optical coherence tomography

Abstract: Despite grossly similar AS architecture, the three groups of reptiles in the study demonstrated differences that are suggestive of a link between anatomical disparities and variations in environment and lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…In this study, the mean CCT value was 177.6 µm, which was higher than that of a nocturnal leopard gecko, as observed using OCT in the previous study (75 µm) 11 . The CCTs in other diurnal saurian species ranged from 50 to 200 µm 11 .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In this study, the mean CCT value was 177.6 µm, which was higher than that of a nocturnal leopard gecko, as observed using OCT in the previous study (75 µm) 11 . The CCTs in other diurnal saurian species ranged from 50 to 200 µm 11 .…”
Section: Discussioncontrasting
confidence: 55%
“…The relationship between retinal structure abnormalities and vision‐related diseases including retinal dysplasia, 8 progressive retinal atrophy, 9 sudden acquired retinal degeneration syndrome (SARDS), 10 and glaucoma 3 has been studied in dogs. There are a few studies on reptilian species (saurians, ophidians, and chelonians) 11,12 . However, to our knowledge, those studies only obtained images of the cornea and anterior chamber, and there are no published studies of OCT parameters in the posterior segment of the reptilian eye.…”
Section: Introductionmentioning
confidence: 99%
“…In all reptiles, the dilated pupil is close to circular (Walls, 1942;Mann, 1931;Werner, 1967), but on illumination pupil shape varies widely. It ranges from circular in all testudines (Mann, 1931;Granda et al, 1995;Rival et al, 2015), some snakes (Mann, 1931;Werner, 1970;Brischoux et al, 2010), and many lizards (Mann, 1931;New et al, 2012), to a narrow vertical slit in many snakes (Mann, 1931;Walls, 1942;Werner, 1967;Brischoux et al, 2010), crocodylians (Mann, 1931;Allen & Neill, 1950;Walls, 1942), and in sphenodontia (Mann, 1931). Horizontally slit pupils are less common in reptiles, but occur, for example, in some tree snakes (Mann, 1931;Heath et al, 1969).…”
Section: Pupil Shapementioning
confidence: 99%
“…An animal whose eye is adapted for vision in low light levels by, for example, the possession of a tapetum lucidum and a retina dominated by sensitive rods, may be compromised in daylight if it relied on a circular pupil. Slit-like pupils among terrestrial species are therefore usually found in predominantly nocturnal animals that nevertheless are sometimes abroad during the day (Walls, 1942;Mann, 1931;Brischoux et al, 2010;Rival et al, 2015;Banks et al, 2015). Strictly diurnal or nocturnal terrestrial animals, on the other hand, tend to have circular pupils, as they would derive less benefit from being able to adapt to a wide range of illumination.…”
Section: Allow a Greater Range Of Aperture Sizesmentioning
confidence: 99%
“…Also, snakes have round lenses that move toward and away from the retina to focus [15,28,30] . The present study revealed that the lens of T. mutabilis has a spherical like most of reptilian species [31,32] .…”
Section: Discussionmentioning
confidence: 52%